One bout of vibration exercise with vascular occlusion activates satellite cells. Issue 2 (1st February 2016) - Aguayo, David; Mueller, Sandro Manuel; Boutellier, Urs; Auer, Maria; Jung, Hans H.; Flück, Martin; Toigo, Marco
Abstract : New Findings: What is the central question of this study? Acute skeletal muscle satellite cell (SC) activation is associated with skeletal muscle hypertrophy. Although the quantity of SCs has been reported to increase following a single bout of resistance exercise, data on muscle fibre type‐specific SC quantity and/or activation status after a single bout of vibration is presently lacking. What is the main finding and its importance? By determining SCs from muscle biopsies of the vastus lateralis using immunohistochemistry, we conclude that modification of vibration exercise by superimposition of occlusion induced activation and differentiation of SCs in young men, which had not been observed with whole‐body vibration or blood flow restriction alone. We tested the hypothesis that whole‐body vibration (WBV) is insufficient to expand satellite cell numbers 24 h postexercise, whereas WBV in combination with blood flow restriction (BFR) is sufficient. Twenty‐five young men were randomly assigned to one of the following three groups: WBV, BFR exercise or WBVBFR. Satellite cell numbers were determined from muscle biopsies of the vastus lateralis muscle using immunohistochemistry. Satellite cell quantity and frequency (+99.4%, P  = 0.012 and +77.1%, P  = 0.010, respectively) increased only in the WBVBFR group. Similar results were obtained for the quantity and frequency of myogenin‐positive myonuclei (+139.0%, P  < 0.001 and +148.4%, P  < 0.001, respectively). We conclude that modification of WBV by superimposition of BFR induced activation and differentiation of satellite cells in young men, which had not been observed with WBV or BFR alone. These data suggest that WBVBFR might represent a novel viable anabolic stimulus. Abstract :